Oppression and Violent Resistance of David Martinez and Its Impact in Cyberpunk: Edgerunners Towards Arasaka - William Jason Budiman; Liliek Soelistyo (Institute of Research and Community Outreach - Petra Christian University, 2024)
This thesis explores how oppression and violent resistance are portrayed in the anime Cyberpunk: Edgerunners through the character of David Martinez. Using Iris Marion Young's